PENGARUH PERSAINGAN AUDITOR, LAMA PENUGASAN (AUDIT TENURE) DAN SIFAT MACHIAVELLIAN PADA INDEPENDENSI AUDITOR: (STUDI EMPIRIS KANTOR AKUNTAN PUBLIK DI BALI) - Artini, Kadek Ayu; Yuniasih, Ni Wayan (Hita Akuntansi dan Keuangan, 2021)
A public accountant most has a sense of self-discipline so that when checking the financials statementses of each company there is no mistake in determining opinions for consumer financial statements. The populated in this study where alls auditor's at the public accounting firm on Bali, namely ninety four people. The sample use in this study were sixty four auditors. The sampling method was purposives samplings technique. Results this reasearch indicated thats auditor competition and audit tenure haven a positive effect, while the machiavellian nature has a negative effect.